2020
DOI: 10.21276/apalm.2704
|View full text |Cite
|
Sign up to set email alerts
|

Non-Neoplastic Testicular and Paratesticular Lesions Study from A Remote Indian Island

Abstract: Non-Neoplastic Testicular and Paratesticular Lesions -Study from A Remote Indian Island IntroductionTestis can be involved by various pathologies and affect a wide age range. In young patients, the common indications for orchidectomy are predominantly non-neoplastic lesions like cryptorchidism, epididymo-orchitis, and torsion of testis. In middle and older age, common indications are pyocele, chronic haematocele, uneducable or recurrent hernia, unsalvageable testicular trauma and Fournier's gangrene. Bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…In our study, 31 to 40 years was the common age group for neoplastic testicular (50%). (Table 1) This was in agreement with various studies Gargade et al 7 Tekumalla et al 13 and Mansi Sharma et al 8 The most common neoplastic Testicular lesion studied in our study was mixed germ cell tumor (75%). (Table 3 ) This is consistent with the study conducted by Sheeja et al 11 The most common neoplastic testicular lesion studied in other studies were mostly seminoma.…”
Section: Comparison Of Spectrum Of Lesions In Testissupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, 31 to 40 years was the common age group for neoplastic testicular (50%). (Table 1) This was in agreement with various studies Gargade et al 7 Tekumalla et al 13 and Mansi Sharma et al 8 The most common neoplastic Testicular lesion studied in our study was mixed germ cell tumor (75%). (Table 3 ) This is consistent with the study conducted by Sheeja et al 11 The most common neoplastic testicular lesion studied in other studies were mostly seminoma.…”
Section: Comparison Of Spectrum Of Lesions In Testissupporting
confidence: 93%
“…Mostly the presentation was in young patients aged <40 years (67.3%). This was consistent with studies conducted by Gargade et al, 7 Mansi Sharma et al, 8 Hemavathi Reddy et al 9 and Sundari et al, 10 who suggested that the maximum number of cases in their study belonged to <40 years age group.…”
Section: Age Wise Distribution Of Casessupporting
confidence: 91%
See 2 more Smart Citations
“…From benign congenital diseases to life-threatening cancers and acute surgical emergencies, testicular and paratesticular lesions can represent a wide spectrum of medical difficulties. 1 These lesions affect people of all ages, with scrotal swelling and pain being the most common In the absence of epididymitis, orchitis manifests as testicular swelling and pain. The onset is usually abrupt and might be unilateral or bilateral in nature.…”
Section: Introductionmentioning
confidence: 99%